2013
DOI: 10.4085/1062-6050-48.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of the Star Excursion Balance Test

Abstract: When the raters have been trained by an experienced rater, the SEBT is a test with excellent reliability when used across multiple raters in different settings. This information adds to the body of knowledge that exists regarding the usefulness of the SEBT as an assessment tool in clinical and research practice. Establishing excellent interrater reliability with normalized and nonnormalized scores strengthens the evidence for using the SEBT, especially at multiple sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 23 publications
0
107
1
8
Order By: Relevance
“…Furthermore, the inter-rater reliability of the HSEBT was high, with ICC values ranging from 0.90 to 0.98. FR inter-rater ICC values between 0.73 and 0.98 have been reported [22,27,28], while SEBT values range from 0.81 to 0.93 [21,24,26,29]. Even though our ICC results showed high HSEBT inter-rater reliability, the repeated measure ANOVA results suggested that in five of the 20 tests at least one rater differed systematically from the other raters ( Table 2).…”
Section: Discussioncontrasting
confidence: 44%
“…Furthermore, the inter-rater reliability of the HSEBT was high, with ICC values ranging from 0.90 to 0.98. FR inter-rater ICC values between 0.73 and 0.98 have been reported [22,27,28], while SEBT values range from 0.81 to 0.93 [21,24,26,29]. Even though our ICC results showed high HSEBT inter-rater reliability, the repeated measure ANOVA results suggested that in five of the 20 tests at least one rater differed systematically from the other raters ( Table 2).…”
Section: Discussioncontrasting
confidence: 44%
“…This measurement has been shown to exhibit excellent intrarater and interrater reliability. 9,23 Composite scores were calculated as the average of the individual normalized reach distances for each direction. Side-to-side differences in reach distance (asymmetry) were calculated for each trial in each direction and for the composite score as the absolute difference in reach distance (centimeters) between limbs.…”
mentioning
confidence: 99%
“…The popularity of the different SEBT protocols is mainly based on their relative low cost and ease of use in comparison to posturographic tests, as well as on their within-session reliability [1,3,[7][8][9] and their applications to injury prevention in clinical, sport, and research settings [10][11][12][13][14][15][16][17]. In this sense, low SEBT scores have been related with several injuries, such as recurrent ankle sprain and chronic instability [13][14][15]18], anterior cruciate ligament injury [11,16,17,19,20], and chronic low-back pain [12].…”
Section: Introductionmentioning
confidence: 99%